2011
DOI: 10.1016/j.molcel.2011.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Cdh1 Regulates Osteoblast Function through an APC/C-Independent Modulation of Smurf1

Abstract: Summary The APC/Cdh1 E3 ubiquitin ligase plays an essential role in both mitotic exit and G1/S transition by targeting key cell cycle regulators for destruction. There is mounting evidence indicating that Cdh1 has other functions in addition to cell cycle regulation. However, it remains unclear whether these additional functions depend on its E3 ligase activity. Here we report that Cdh1, but not Cdc20, promotes the E3 ligase activity of Smurf1. This is mediated by disruption of an auto-inhibitory Smurf1 homodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
114
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(124 citation statements)
references
References 43 publications
8
114
2
Order By: Relevance
“…During the rest of the cell cycle, Cdh1 is largely APC free [28]. Our previous study has demonstrated that APC-free Cdh1 augments Smurf1 E3 ligase activity to govern osteoblast differentiation [17]. In the present study, we identified Gsc as a new substrate of APC Cdh1 and further revealed a novel role for Cdh1 in craniofacial development through promoting APC-dependent, non-proteolytic ubiquitination and activation of Gsc. It has been well characterized previously that APC promotes substrate ubiquitination in two distinct steps by associating with two different E2-conjugating enzymes, UBCH10 and Ube2S, which leads to initial monoubiquitination and subsequent K11-linkage polyubiquitination [29].…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…During the rest of the cell cycle, Cdh1 is largely APC free [28]. Our previous study has demonstrated that APC-free Cdh1 augments Smurf1 E3 ligase activity to govern osteoblast differentiation [17]. In the present study, we identified Gsc as a new substrate of APC Cdh1 and further revealed a novel role for Cdh1 in craniofacial development through promoting APC-dependent, non-proteolytic ubiquitination and activation of Gsc. It has been well characterized previously that APC promotes substrate ubiquitination in two distinct steps by associating with two different E2-conjugating enzymes, UBCH10 and Ube2S, which leads to initial monoubiquitination and subsequent K11-linkage polyubiquitination [29].…”
Section: Discussionsupporting
confidence: 56%
“…Besides its conventional roles in cell cycle regulation, Cdh1 has recently been found to play critical roles in a wide spectrum of cellular processes including DNA damage repair [9,12], cellular metabolism [13], cell migration [14] and neuronal development [15,16]. Moreover, we recently identified a novel, APC-independent, role for Cdh1 in controlling osteoblast differentiation by disrupting the inter-molecular interaction of Smurf1 dimers, leading to the activation of Smurf1, another member of the NEDD4 family of E3 ligases [17].…”
Section: Cdc20mentioning
confidence: 99%
“…Cdh1, a subunit of the Anaphase promoting complex, was reported to bind C2 and the WW1 domain of SMURF1. Such an interaction also leads to SMURF1 activation, possibly by disrupting SMURF1 homodimer formation (49). Cerebral cavernous malformation 2 recognizes the HECT domain of SMURF1 and helps to localize SMURF1 to the plasma membrane to enhance RhoA ubiquitination and degradation (50).…”
Section: Discussionmentioning
confidence: 99%
“…This result suggested that each of the three domains was required for the interaction between Smurf1 and Stk38. Similarly as many other E3 ubiquitin ligases, activation of Smurf1 was dependent on ubiquitination of itself 27 . Thus, we detected the effect of Stk38 on Smurf1 ubiquitination.…”
Section: Stk38 Inhibits Tlr9-mediated Inflammatory Responsesmentioning
confidence: 98%